PEMANFAATAN OPEN SOURCE GOOGLE EARTH UNTUK PERENCANAAN JALAN KABUPATEN MAJALENGKA - Nur Azizah Fitriani (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Google Earth is a digital map that contains live satellite images. Satellite digital maps are displayed by Google Earth at different resolutions. The use of Open Source Google Earth is widely used by researchers because of its ease of access and real conditions. One of the uses of Google Earth is used for Road Planning Majalengka District. The result obtained is That Google Earth is proven to be used as a road planning material for Majalengka District.